In Vitro Matured Human Pluripotent Stem Cell–Derived Cardiomyocytes Form Grafts With Enhanced Structure and Function in Injured Hearts. Issue 18 (28th January 2022) - Dhahri, Wahiba; Sadikov Valdman, Tamilla; Wilkinson, Dan; Pereira, Elizabeth; Ceylan, Eylül; Andharia, Naaz; Qiang, Beiping; Masoudpour, Hassan; Wulkan, Fanny; Quesnel, Elya; Jiang, Wenlei; Funakoshi, Shunsuke; et al.
Abstract : Background: Human pluripotent stem cell (hPSC)–derived cardiomyocytes (hPSC-CMs) have tremendous promise for application in cardiac regeneration, but their translational potential is limited by an immature phenotype. We hypothesized that large-scale manufacturing of mature hPSC-CMs could be achieved through culture on polydimethylsiloxane (PDMS)-lined roller bottles and that the transplantation of these cells would mediate better structural and functional outcomes than with conventional immature hPSC-CM populations. Methods: We comprehensively phenotyped hPSC-CMs after in vitro maturation for 20 and 40 days on either PDMS or standard tissue culture plastic substrates. All hPSC-CMs were generated from a transgenic hPSC line that stably expressed a voltage-sensitive fluorescent reporter to facilitate in vitro and in vivo electrophysiological studies, and cardiomyocyte populations were also analyzed in vitro by immunocytochemistry, ultrastructure and fluorescent calcium imaging, and bulk and single-cell transcriptomics. We next compared outcomes after the transplantation of these populations into a guinea pig model of myocardial infarction using end points including histology, optical mapping of graft- and host-derived action potentials, echocardiography, and telemetric electrocardiographic monitoring. Results: We demonstrated the economic generation of >1×10 8 mature hPSC-CMs per PDMS-lined roller bottle. Compared with their counterparts generated on tissue culture plastic substrates, PDMS-matured hPSC-CMs exhibited increased cardiac gene expression and more mature structural and functional properties in vitro. More important, intracardiac grafts formed with PDMS-matured myocytes showed greatly enhanced structure and alignment, better host-graft electromechanical integration, less proarrhythmic behavior, and greater beneficial effects on contractile function. Conclusions: We describe practical methods for the scaled generation of mature hPSC-CMs and provide the first evidence that the transplantation of more mature cardiomyocytes yields better outcomes in vivo.